Competition and profitability of Sharia rural banks in Indonesia - Pamikatsih, Mutia; Purwanto, Purwanto (Economics, Finance, and Business Review, 2025)
The purpose of this study is to analyze the influence of market forces, measured by the Lerner Index, on the profitability (ROA) of Sharia Rural Banks (SRBs) in Indonesia, as well as to test the validity of the Structure–Conduct–Performance (SCP) Hypothesis and the Efficient Structure Hypothesis (ESH). Using Fixed Effect Model (FE) panel data regression, this study involved all SRBs and analyzed SRBs separately based on asset size (large vs. small). The estimated results show that overall, market forces have a positive and significant influence on ROA, providing strong support for the SCP Hypothesis. The heterogeneity analysis revealed a crucial finding: the influence of market forces is much more dominant on Small SRBs, which shows a greater ability to exploit the concentration of local markets. On the other hand, the profitability of Large SRBs is also driven by internal efficiency (supporting ESH), and has proven to be more resistant to external shocks (COVID-19) than Small SRBs. Financing risk factors (NPF) and capital adequacy (CAR) are the pressures of profitability in all segments. These findings imply that the SCP/ESH debate depends on the scale of SRB, thus demanding the need for differentiated oversight policies to improve SRB's resilience and efficiency.